ANALISA PENGARUH PENERAPAN SUMBER DAYA PERUSAHAAN UNTUK MENINGKATKAN KINERJA MANAJEMEN RANTAI PASOK PADA PT. MAYORA INDAH TBK - Davin Ewaldo; Michael Setiawan; Viviana Angesty; Lina; Fendy Chuandra; Marliana (Transpublika Publisher, 2023)
This study aims to evaluate the impact of ERP implementation on PT Mayora Indah Tbk. A qualitative approach and internet search method were used in this research to collect as much data as possible related to the topic under study, including data from the internet and related journals. Data analysis was conducted to evaluate the effect of ERP on the performance of PT Mayora Indah Tbk, especially in improving production levels and product quality, as well as delivery accuracy supported by the ERP system implemented in the company. The research findings show that ERP implementation has a significant influence in improving the performance of PT Mayora Indah Tbk. Suggestions that can be given to the results of this study are that researchers can include a more detailed analysis of the effect of ERP systems on supply chain management. This research contributes to the academic study of ERP and provides important insights for business practitioners. The implications of this research can be used by other companies that want to improve performance through ERP implementation.